Impact of Leadership, Discipline, and Organizational Commitment on the Effectiveness of Teacher Work - Masnawati, Eli; Hariani, Mila (Bulletin of Science, Technology and Society, 2023)
This study aims to investigate the influence of leadership, discipline, and organizational commitment on the effectiveness of teacher work in several elementary schools in Gresik Regency. The effectiveness of teacher work is measured based on the quality of learning, understanding of the individual needs of students, and the ability to create an inclusive learning environment. The research method used a quantitative approach with associative methods, and data was collected through literature studies, field studies, and filling out questionnaires by 64 teachers from four elementary schools. Multiple linear regression analysis is used to evaluate the effect of independent variables on the effectiveness of teacher work. The results show that leadership, discipline, and organizational commitment together have a significant effect on the effectiveness of teacher work. Individually, all three independent variables also had a significant positive influence. The implications of this study provide an in-depth understanding of the factors that can improve the effectiveness of teacher work, taking into account aspects of leadership, discipline, and organizational commitment.